Late-Holocene cliff-top blowout activation and evolution in the Cooloola Sand Mass, south-east Queensland, Australia. (November 2018) - Ellerton, Daniel; Rittenour, Tammy; Miot da Silva, Graziela; Gontz, Allen; Shulmeister, James; Hesp, Patrick; Santini, Talitha C; Welsh, Kevin J
Cliff-top dunes are a locally important geomorphic features of sedimentary coasts. They are traditionally interpreted as being sourced by (or with) sand derived from the beach below the cliff. This paper presents the results of a stratigraphic and geochronological study of Carlo Sand Blow, a coastal blowout that has developed on top of a high sandy cliff in the Cooloola Sand Mass, south-east Queensland. We use a combination of sedimentological, pedological and geophysical techniques along with optically stimulated luminescence dating to determine the depositional history and evolution of the blowout. We demonstrate that the blowout is dominantly nourished by sand eroded from its floor rather than the adjacent beach. The original dune surface dates to the first half of the last glacial period (c. 40–70 ka) and this dune was deflated in the late-Holocene. Dune activity is directly associated with cliff undercutting because of coastal retreat in the late-Holocene, but coastal erosion on its own is not capable of maintaining aeolian activity. Blowout activity occurred between 2.6 and 2.3 ka and again at 0.3 ka with aeolian sand burying palaeosols. Both soil surfaces contained charcoal and tree stumps in growth position and our study suggests that fire is the immediate trigger for blowout reactivation. It is likely that these fires were anthropogenic in origin, because the site is somewhat protected from natural fire and the ages coincide with intensification of human use of coastal sites in the area.